Stable isotopes of Uvigerina spp. from sediment core M78/1_235-1 - Dirk Nürnberg; Tabitha Riff; André Bahr; Cyrus Karas; Karl J F Meier; Jörg Lippold (PANGAEA, 2021)
Stable carbon (δ13C) and oxygen isotope (δ18O) were performed on the benthic foraminiferal species Uvigerina spp. The foraminiferal specimens were selected from piston core M78/1-235-1, which was recovered from Tobago Basin (11°36.53 extquotesingleN 60°57.86 extquotesingleW) from 852 m water depth during R/V Meteor Cruise 78/1. Sampling and analytical studies were carried out from 412.5 to 800 cm core depth at 2-4 cm spatial resolution. This dataset extends the existing benthic proxy records (Poggemann et al., 2017; doi:10.1029/2018PA003376) further back in time, now focusing on the glacial time period and the latest fully developed D/O events (~22.7-37 ka BP). The isotope analyses were performed in 2017 and 2019 on a Thermo Scientific MAT 253 mass spectrometer with an automated Kiel IV Carbonate Preparation Device. The proxy data provide stratigraphical information on the Tobago Basin core M78/1-235-1.